MENGUAK IMPLEMENTASI PRINSIP GOOD GOVERNMENT GOVERNANCE DALAM PENGELOLAAN DANA DESA: SEBUAH UPAYA PENCEGAHAN FRAUD - Wa Ode Rayyani; Jumiati Jumiati; Sunarti Sunarti (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
This study aims to determine how the implementation of the principles of Good Governance Government in the management of village funds as an effort to prevent fraud in Toddotoa Village, Pallangga District, Gowa Regency. Toddotoa Village is one of the villages in Gowa Regency that receives a relatively large allocation of village funds compared to other villages and experiences an increase in the allocation every year. The research approach with qualitative research uses a case study method in which desk study and field study with interviews and observations in order to collect data. The results showed that Toddotoa Village had synergized well in applying the principles of Good Government Governance. In order to achieve Good Government Governance as an effort to prevent fraud, the three pillars of Good Government Governance namely accountability, transparency and participation are well implemented through concrete actions in the form of injecting Good Government Governance values ​​in the practice of organizing village fund management so as to minimize, even prevent the occurrence of fraud in managing village funds.